Factors Affecting Quality of Life of Persons Treated for Narcotic Drug Use in Primary Care Hospitals, Udon Thani Province - Soongkhang, Supranee (Journal of Health Science of Thailand, 2017)
The objectives of this study were to evaluate a rehabilitative program for narcotic drug users in primary care hospitals in Udon Thani Province, Thailand; and to analyze the relationship and factors affecting quality of life of the patients who had been treated for 1 year, and were followed up by subdistrict health promoting hospitals in the province. There were1,156 patients recruited through simple random sampling procedure. Data on quality of life (QOL) indicators were collected during March -September 2014 using a set of questionnaire. Quantitative data analysis was conducted using frequency, percentages, mean, median, standard deviation, and chi-square test. Multiple logistic regression was applied to determine and estimated Odds Ratio and 95% confidence interval for QOL indicators with significant level 0.05. It was found that most patients were male (98.6%), 15-19 years old (36.8%), with the median monthly income of 3,000 baht. Treatment duration was mainly below 3 years (99.8%). Majority of them (88.7%) received family support during the treatment; and 93.0% had at least one follow-up. The main narcotic substance used in the past 1 month was alcohol (50.9%) in order to gain more power to work. After complete one-year treatmet and rehabilitation, 58.4% reported improvement of quality of life; 90.8% had better physical health; and 98.0% could resume normal working or studying function. Ninety percent of them were able to stop drug consumption. It was also found that factors significantly associated with QOL of the patients were poor group behavior influences to QOL at 5.2 times (CI: 0.257-0.770), stress group at 2.8 times (CI: 0.665-0.784), stop abuse at 2.8 times (CI: 0.230-0.572), poor group behavior at 2.3 times (CI: 0.913-0.991). In addition, there were factors that significantly influenced the QOL with lower power (less than 2 times) including the age group 20-24 years, unemployment, no interest in community environment, income lower than 5,000 baht, BMI <18 /≥ 23, gender, education lavel, mental health, poor physical health, number of follow up and family care. In conclusion, the findings illustrated that family care and community participation could be effective for drug users to discontinue drug use, self support, and improve quality of life.